Apatinib attenuates phenotypic switching of arterial smooth muscle cells in vascular remodelling by targeting the PDGF Receptor‐β - Shao, Wenchao (J Cell Mol Med, 2020)
Apatinib (YN968D1) is a small‐molecule tyrosine kinase inhibitor（TKI）which can inhibit the activity of vascular endothelial growth factor receptor‐2 (VEGFR‐2). It has been reported that apatinib has anti‐tumour effect of inhibiting proliferation and inducing apoptosis of a variety of solid tumour cells, whereas its effect on vascular smooth muscle cells (VSMC) remains unclear. This study investigated the effect of apatinib on phenotypic switching of arterial smooth muscle cells in vascular remodelling. Compared to the vehicle groups, mice that were performed carotid artery ligation injury and treated with apatinib produced a reduction in abnormal neointimal area. For in vitro experiment, apatinib administration inhibited VSMC proliferation, migration and reversed VSMC dedifferentiation with the stimulation of platelet‐derived growth factor type BB (PDGF‐BB).In terms of mechanism, with the preincubation of apatinib, the activations of PDGF receptor‐β (PDGFR‐β) and phosphoinositide‐specific phospholipase C‐γ1 (PLC‐γ1) induced by PDGF‐BB were inhibited in VSMCs. With the preincubation of apatinib, the phosphorylation of PDGFR‐β, extracellular signal‐related kinases (ERK1/2) and Jun amino‐terminal kinases (JNK) induced by PDGF‐BB were also inhibited in rat vascular smooth muscle cell line A7r5. Herein, we found that apatinib attenuates phenotypic switching of arterial smooth muscle cells induced by PDGF‐BB in vitro and vascular remodelling in vivo. Therefore, apatinib is a potential candidate to treat vascular proliferative diseases.